Pemanfaatan Arang Tempurung Kelapa Teraktivasi Sebagai Penyerap Bau di Kelurahan Sungai Salak - Zurfan Suri; Fatimah F; Galuh Dian Pramesti; M. Ziri Ramadhan; Riski Agustian; Tamaria Sinaga; Mhd. Nouval Fazammi; Gusnita Mayasari Siregar; Viona Rossalia; Yulia Ariani (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Sungai Salak Village, Tempuling District, Indragiri Hilir Regency, is one of the largest coconut-producing areas in Riau Province, generating abundant coconut shell waste. However, this waste is generally used only as fuel or discarded, resulting in limited economic value for the local community. This community service program aimed to improve the knowledge and skills of community members in utilizing coconut shell waste by converting it into activated charcoal as the primary material for producing Air Fresh Bags, an environmentally friendly and value-added natural odor absorber. The implementation methods included field observation, socialization, product demonstrations, hands-on training, and interactive discussions. The production process consisted of raw material preparation, carbonization of coconut shells, grinding, sieving, physical activation at 110–120°C for 30–40 minutes, cooling in a sealed aluminum container, and packaging the activated charcoal into cotton fabric bags. The program involved 25 participants out of 30 invited community members and successfully produced 10 Air Fresh Bag products as the training output. The results demonstrated that participants improved their knowledge and practical skills in processing coconut shell waste into an innovative product capable of absorbing odors in enclosed spaces, such as wardrobes, shoe racks, drawers, and vehicle interiors. In addition to increasing the economic value of organic waste, this program contributed to community empowerment, the development of local resource-based microenterprises, and environmental sustainability through the effective utilization of coconut shell waste.